Administrative order of the legal regulation of economic activity in Ukraine - Власюк, Алла Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article deals with the administrative order of the legal regulation of economic activity in Ukraine according to the current legislation. Also attention is focused on the concept of «state registration» that is determined differently by the legislator. The role of government regulation is always significant: on the stage of market interactions and when market relations are already established. This approach is more in line with current realities of management. The key role of the state in regulating economic processes seems indisputable. The purpose of the article is consisted of analysis of the administrative and legal regulations for conducting business activities in Ukraine. There are a number of problems in the administrative and legal regulations of the order of the economic activities in Ukraine: unstable legislation, ambiguity of understanding of the legal norms, lack of transparency of licensing procedures, unfounded existence of a huge amount of existing permits, duplication of responsibilities and functions of licensing authorities, irregular order of interaction of various authorities in the discharge of their functions.